The Role of Impulsivity and Self-Control in Decision Making in Adolescence: Array - Manea , Cosmina-Marilena (New Trends in Psychology, 2021)
Impulsivity, self-control, and decision-making capacity are no longer fully mastered during adolescence due to the influences of bio-psycho-socio-cultural factors. Thus, a low level of self-control and an increased level of impulsivity make adolescents no longer have the ability to make optimal decisions. If the proportions of these traits are reversed then adolescents can choose the optimal decision that brings the greatest benefits. The 110 adolescents were tested using the translated version of the UPPS-P Test, the Self-Control Scale on the CPI Test Card, and the Decision Ability Test in the Battery of Psychological Cognitive Aptitude Tests (BTPAC).